Tinjauan Literatur: Evaluasi Program Jaminan Kesehatan Nasional (JKN) di Indonesia - Nugraheni, Aghesta Intan; C. Ermayani Putriyanti; Kurnianto, Andreas (Jurnal Kesehatan, 2023)
The National Health Insurance (Jaminan Kesehatan Nasional/ JKN) program is a health insurance program that is able to change the health system in Indonesia. The coverage of the entire Indonesian population has reached 93% or around 258.3 million people from 2013 to 2021. However, in its implementation there are still challenges and obstacles in several areas in Indonesia. Complaints from the community, health workers, and health service facilities are also often found. This study aims to describe about the sustainability of the JKN program in improving the health care system in Indonesia and provide an evaluation of the implementation of the JKN program obtained through literature review from various journal sources. This study is a literature review where previous studies are collected and reviewed. The articles were searched through Google Scholar databases using the keywords JKN evaluation, JKN program, JKN implementation, and by applying restrictions on the year of publication (2020-2023). There were ten articles that met the criteria.  Based on the evaluation of the National Health Insurance (JKN) program in Indonesia, there are several problems in its implementation. Therefore, the government needs to conduct monitoring, evaluation, and action to improve the effectiveness of the JKN program in improving the health care system in Indonesia.